Design and development of organolead halide perovskite solar cells - Yılmaz, Beyza. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The aim of this thesis was to design and develop organolead halide perovskite solar cells by employing cost efficient and easily generated materials via industrially applicable processes. In the experiments, two kinds of perovskite solar cells were fabricated in terms of their device configurations. First, TiO2 electron transport material based n-i-p type planar perovskite solar cells were produced. Using both single and sequential deposition techniques, methylammonium lead iodide (MAPbI3) perovskite was coated on TiO2. PCBM and ZnO charge carriers were applied on perovskite surface by spin coating. The PSCs were completed with the addition of Al and Cu conductive tapes as back contact of the device. The other design was inverted planar PSC. This device was fabricated based on p-type NiO conductive material. NiO was spun on ITO substrates as hole transporting material. The second layer of the device was also MAPbI3 perovskite which was synthesized by both one-step and two-step deposition methods. However, one-step deposited PSCs with NiO as HTM did not work due to insufficient surface coverage. The next step was the coating of ZnO and ionic liquid electron transport materials on perovskite crystals. On the other hand, ETL-free solar cells were also fabricated. All devices with NiO as HTM were finished with attachment of Al and Cu tapes which were the back electrode of the structure. In addition, NiO/MAPbI3/ZnO configurated device was arranged to contain Au electrode deposited by sputtering method. All coating operations were performed by spin coating method under ambient conditions. The PSCs were measured by using Keithley 2401 Source Meter at 100 mW/cm2 irradiance of ABET LS 150 Xenon Lamp Source solar simulator. The PSC with the best efficiency which was 7.27×10−3% had the configuration as NiO/MAPbI3/ZnO/Al. Moreover, this device demonstrated electrical characteristics of 0.51 V open circuit voltage, 27.3% fill factor and 0.052 mA/cm2 short circuit current density. The results are very low compared to literature due to perovskite degradation originated from high humidity of air.
Keywords: Solar cells -- Design and construction.; Perovskite.